Planning of water resources according to innovative solutions - نصير عبد الرزاق حسج البصري / سامر هادي كاظم الجشعمي ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Innovative planning is one of the most important subjects which had been popular lately among specialized scientific and research community, , especially being based on the principle of using information technology And techniques described as smart, innovative ways and solutions more efficiently than conventional solutions that used city and regional administrations on its proposal and application.Because of water resources importance , multiplicity various types and components in development through their impact on improving the quality of life and is closely linked to the lives of the population and economic and social activities, and to work at the core of human interests, so it became necessary to highlight innovative planning approach based on the principle of governance and high technological solutions and formulate a curriculum management and planning, Particular question is the sustainability of water resources and minimize the environmental impacts of resource use issues through a review of innovative indicators and some models and global experiences and methods and innovative solutions in this regard to access content and desired results and present working directory Policy and contribute to the sustainability of water